Educational Tourism and Community-Based Ecotourism: Diversification for Tourist Education - Andari, Rini (Journal of Tourism Education, 2023)
The era of globalization has an influence on various areas of life, a lack of belonging to the local culture and environment can result in damage to nature and culture. Educational tourism becomes a unity between tourism and education that can improve the education system, improve the competitiveness of the younger generation and develop human resources for the better. The purpose of this study is to understand how the results of educational tourism for education based on eco-tourism and community based tourism. This research used qualitative to uncover the meaning of research results with case study techniques. The results of exploration of the educational tourism in the Kampung Adat Banceuy can be grouped in the form of community life and rural atmosphere as educational tourism, community based tourism (CBT), and educational and eco-tourism. Educational tourism can provide benefits in addition to tourists as well as for researchers, where recreation can be done while learning directly with the local community. The presence of Kampung Adat Banceuy provides new learning opportunities as well as teaching the value of life, especially to maintain nature and culture.